2015
DOI: 10.1021/acs.chemmater.5b01845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Orientation and Spontaneous Interfacial Mixing on the Performance of Organic Solar Cells

Abstract: A critically important question that must be answered to understand how organic solar 3 cells operate and should be improved is how the orientation of the donor and acceptor 4 molecules at the interface influences exciton diffusion, exciton dissociation by electron transfer and recombination. It is exceedingly difficult to probe the orientation 6 in bulk heterojunctions because there are many interfaces and they are arranged with 7 varying angles with respect to the substrate. One of the best ways to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…[67,68] Interestingly, in the case of PIPCP/ C 60 , the J SC in fact decreases with thermal annealing. This may explain the lower V OC in the bilayer devices, 0.76 V, and the greater E g -qV OC = 0.71 eV.…”
Section: Bilayer Solar Cells Achieve High Ffmentioning
confidence: 97%
“…[67,68] Interestingly, in the case of PIPCP/ C 60 , the J SC in fact decreases with thermal annealing. This may explain the lower V OC in the bilayer devices, 0.76 V, and the greater E g -qV OC = 0.71 eV.…”
Section: Bilayer Solar Cells Achieve High Ffmentioning
confidence: 97%
“…We have fabricated bilayer solar cells using a-rubrene, t-rubrene, and o-rubrene as the donors, and C 60 as the acceptor (glass/ITO-150 nm/rubrene-50 nm/ C 60 -50 nm/Bphen-12 nm/Al-100 nm, Figure 2b). The CuI layer, which has been shown to act as an effective seed layer for the growth of several organic donors, [36][37][38] had the benefit of maintaining the continuity of the rubrene films even after crystallization. The CuI layer, which has been shown to act as an effective seed layer for the growth of several organic donors, [36][37][38] had the benefit of maintaining the continuity of the rubrene films even after crystallization.…”
Section: Structural Order In Rubrene Thin Films and Its Influence On mentioning
confidence: 99%
“…The evaporated molecules could diffuse into the bottom layer owing to their high kinetic energy, and a thin mixed interlayer could be formed between the two layers . The situation is complicated further by recent experimental and theoretical studies suggesting that the degree of diffusion might depend on the miscibility of the two materials, the orientation of the bottom layer, and the temperature of the substrate during the deposition . These factors should be considered in the construction of heterointerfaces.…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…More recently, Ngongang Ndjawa et al reported that in PHJs, the degree of intermixing of the donor and acceptor at the vacuum‐deposited interfaces can depend on the molecular orientation in the bottom layer ( Figure ) . They found that when C 60 was deposited on top of a ZnPc layer, the D/A interface suffered from greater intermixing of C 60 with the ZnPc face‐on orientation than with the edge‐on orientation.…”
Section: Photophysical Processes In Organic Photovoltaics Based On Plmentioning
confidence: 99%